Первый день: роман / Марк Леви; [перевод с французского Е. Тарусиной] - Леви Марк (Иностранка, 2012)
Экземпляры: ф. 9 (20120402) / Инвентарный номер: 46727 / Цена: 183.38 / Авт.знак: Л 36 / ГРНТИ: 17.82 / ББК: 84(4Фра)